Ewolucja prawa łaski w Polsce do XVIII w. - Sobiech, Jan (Kwartalnik Prawa Publicznego, 2016)
The functioning of pardon as a specific systemic and criminal institution has long been the subject of interest by criminal law and historians – both in terms of the circle of authorized entities, as well as its scope. Analysis of the evolution of pardon in the Polish legal system allows us to answer many questions related to the practice of political system in past times. In the era of monarchy or patrimonial state you cannot talk about juridically structured institutions of pardon, because for a long time it functioned as a habit, thus giving a strong competence monarchs and local princes in its application. Only in times of an elective monarchy pardon began to be regulated by law, which incurred in significant restriction of royal power in favor of the nobility, and then formed already plenary parliament. It should be realized that the power of reprieve was functioning in this or another political and legal shape for a long time, and his contemporary institutionalization makes de facto reminiscent of prerogatives of former monarchs.